Outcome of childhood bacterial meningitis on three continents - Heikki Peltola (Nature Portfolio, 2021)
Abstract Our objective was to quantify the differences in the outcomes from childhood bacterial meningitis (BM) and to describe the factors associated with them in different parts of the world. This study is a secondary analysis of prospectively collected data from five clinical BM trials conducted in Finland, Latin America (LatAm), and Angola between 1984 and 2017. As all data were collected uniformly, direct comparison of the series was possible. Associations between patient characteristics and death or dismal outcome—the triad of death, severe neurological sequelae, or deafness—were explored. In all, data on 2123 children with BM were analyzed. Etiology was confirmed in 95%, 83%, and 64%, in Finland, LatAm and Angola, respectively. The leading agents were Haemophilus influenzae, Streptococcus pneumoniae, and Neisseria meningitidis. Dismal outcome was the end result for 54%, 31%, and 5% of children in Angola, LatAm, and Finland, respectively. Although underweight, anemia, and tardy arrival worsened prognoses in Angola and LatAm, it was the presenting condition that was central in terms of outcome. In multivariate analysis, the factors independently associated with dismal outcome were the study site (Angola vs. Finland, OR 11.91, 95% CI 5.54–25.63, p < 0.0001 or LatAm vs. Finland, OR 9.46, 95% CI 4.35–20.61, p < 0.0001), Glasgow Coma Score < 13 (OR 4.58, 95% CI 3.31–6.32, p < 0.0001), seizures (OR 1.96, 95% CI 1.43–2.69), age < 1 year (OR 1.55, 95% CI 1.13–2.14, p = 0.007), and pneumococcal etiology (OR 1.49, 95% CI 1.08–2.06, p = 0.015). Greatly dissimilar outcomes from BM reflected the findings on admission on all three continents. Optimizing growth, preventing anemia, and prompt treatment may improve outcomes in resource poor areas.